2022
DOI: 10.1093/rheumatology/keac549
|View full text |Cite
|
Sign up to set email alerts
|

Functional autoantibodies in systemic sclerosis: influence of autologous stem cell transplantation and correlation with clinical outcome

Abstract: Objectives To evaluate the effect of autologous stem cell transplantation (aSCT) on functional antibodies (abs) to the angiotensin II type-1-receptor (AT1R) and topoisomerase-I(topo-I) in systemic sclerosis (SSc)-patients and to analyse their prognostic relevance Methods Forty-three SSc-patients in whom aSCT was performed were analysed. Thirty-one patients had a favourable outcome after aSCT (group 1), 12 patients showed no r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…However, the effect of this scenario on functional Abs against GPCRs is not yet well investigated. A recent study has shown that the reactivity and the levels of functional AT1R Abs are not touched by this therapy ( 101 ). Moreover, despite the advantages of the AHSCT, potential challenges such as providing an optimal therapeutic regimen, limitations in the availability of biomarkers that help in selecting patients who may benefit from transplantation, and late-onset adverse events remain to be determined ( 102 ).…”
Section: Targeting Gpcrs and Respective Abs: A Potential Therapeutic ...mentioning
confidence: 99%
“…However, the effect of this scenario on functional Abs against GPCRs is not yet well investigated. A recent study has shown that the reactivity and the levels of functional AT1R Abs are not touched by this therapy ( 101 ). Moreover, despite the advantages of the AHSCT, potential challenges such as providing an optimal therapeutic regimen, limitations in the availability of biomarkers that help in selecting patients who may benefit from transplantation, and late-onset adverse events remain to be determined ( 102 ).…”
Section: Targeting Gpcrs and Respective Abs: A Potential Therapeutic ...mentioning
confidence: 99%
“…The cause of SSc is unknown, involving genetic, environmental and immunological factors, as well as mechanisms related to cell senescence and inflamm-aging [80]. Up to 95% of patients diagnosed with SSc exhibit the presence of anti-nuclear Abs.…”
Section: Systemic Sclerosis (Ssc)mentioning
confidence: 99%
“…In vitro experiments have revealed that anti-AT1R Abs can elicit specific responses in ECs. They induce the phosphorylation of ERK 1/2 and stimulate the expression of messenger RNA for TGF-β, VCAM-1 and IL-8 [80]. The interaction between receptors, such as the heterodimerization of AT1R and ETAR, can lead to receptor hypersensitization (adapted after [9]).…”
Section: Systemic Sclerosis (Ssc)mentioning
confidence: 99%
See 2 more Smart Citations